sustainability and viability of public debt in Colombia (2014)
This essay is the result of an investigation documentary about the feasibility and sustainability of Colombia ́s public debt. This is looking determined based on the evolution of debt in the decade 2002 to 2012 and its composition for the last year. In the context of the situation and economic reality not only the country but the world , public debt is of vital importance to be one of the primary sources of funding for governments in Latin America in order to acquire resources in order to meet all claims in order to fulfill its social mission. In addition to this during the decade 2002 to 2012 and even today, in Colombia, the Public Debt highlights its importance and relevance after evaluating your progress in this period of time and demonstrates the continuum of the same regular growth. It is also noteworthy, as despite the progress that has submitted the Colombia ́s debt in, the percentage of the Gross Domestic Product GDP has been declining causing debt ratios of the Nation presented a marked improvement, so that Colombia's economy is stronger and see more reliable in the eyes of the global economy and investors.